Integrated Futures Approach to Ensure the Backcasting as a Strategic Approach for Realizing Saudi Vision 2030: The Art of How - Elbortokaly , Amira; Elhassan , Zeinab Abdallah Mohammed (Journal of Ecohumanism, 2025)
This study examines the application of backcasting as a strategic planning tool for achieving Saudi Vision 2030 goals. The research aims to explore how backcasting contributes to urban sustainability, compare it with forecasting techniques, and analyze its integration potential with other futures methods. A comprehensive literature review focused on futures studies methodologies and their application in the context of Saudi Vision 2030. The findings highlight the effectiveness of backcasting in addressing complex challenges and its potential for integration with other futures methods to create robust strategies for Vision 2030 realization. Key challenges identified include stakeholder conflicts and resource constraints. The study concludes that backcasting offers a promising approach to realizing Saudi Vision 2030, particularly when combined with participatory methods and adaptive planning strategies.